Simple Coding Method Application For Dyslexic Student Beginning Reading Skills: Penerapan Metode Simple Coding Untuk Kemampuan Membaca Permulaan Siswa Disleksia - Susanah Susanah; Ibnu Syamsi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Reading constitutes an essential language skill that provides the foundation for academic success, necessitating adaptive instructional practices within inclusive educational settings. Specific Background Students diagnosed with dyslexia frequently experience chronic neurobiological deficits in phonological processing, leading to significant difficulties in distinguishing visually similar letters and blending syllables. Knowledge Gap Despite the known benefits of multisensory learning, limited classroom action research has specifically investigated the Simple Coding Method as a structured visual strategy to guide dyslexic learners from letter recognition to word decoding. Aims This study investigates the application of the Simple Coding Method to elevate the beginning reading skills of first-grade students with dyslexia at an inclusive elementary school. Results Following two instructional cycles, average beginning reading mastery progressed from a baseline of 43.75 percent to 77.08 percent in the first cycle, ultimately reaching 89.58 percent in the second cycle. Participants demonstrated substantial improvements in vowel and consonant identification, syllable blending, reading fluency, and classroom confidence. Novelty This research highlights the practical efficacy of integrating a systematic, color-based visual coding system with explicit phonics instruction and structured parental engagement as a compensatory mechanism for phonological weaknesses. Implications Educational institutions should adopt visual coding as a standard adaptive pedagogical strategy and establish continuous professional training alongside parental cooperation to build supportive literacy environments. Highlights Visual color cues significantly improve phonological decoding and visual discrimination of confusing characters. Average early literacy mastery levels reached 89.58 percent following two adaptive instructional cycles. Structured parental engagement combined with explicit phonics instruction fosters robust academic confidence and participation. Keywords Dyslexia; Visual Coding; Phonological Processing; Inclusive Education; Early Literacy